The shelf-life of black tiger shrimp (Penaeus monodon) treated with the different conditions - Tam, Le Nhat; Vu, Truong Huynh Anh; Hai, Chu Van (Vietnam Journal of Science and Technology, 2019)
This study examines the chemical and microbiological changes and the sensory attributes of black tiger shrimp (Penaeus monodon) when stored at the temperature of 0 ºC. Sodium propionate and sodium lactate were used to treat shrimps before storage. Vacuum packaging was also carefully investigated. Throughout storage, the quality indicates including TVB-N, TMA-N, histamine, quality index (QI) and total viable count (TVC) were used to evaluate the quality changes of shrimp. The results show that though with different rates, the increase in quality indicators caused the decrease in the quality of shrimp during storage. The quality of shrimps treated with salts of organic acids or those packed in the vacuum bags was significantly higher than that of the control. In particular, the shelf-life of the sample packed in the vacuum packages was twelve days, which was four days longer than that of the control.